TELAAH TERHADAP PRESIDENTIAL THRESHOLD DALAM PEMILU SERENTAK 2019 - Ansori, Lutfil (Jurnal Yuridis, 2017)
This paper aims to examine the presidential threshold in relation to the simultaneous general elections 2019. After the decision of the Constitutional Court Number 14/PUU-XI/ 2013 which mandates the general election simultaneously raises the pros and cons of setting the presidential threshold. In the constitutional perspective, using or not using the presidential threshold is not contrary to the constitution, because the presidential threshold is an open legal policy of the legislator. The legislators need to rethink the provisions of the presidential threshold especially in relation to the simultaneous elections, taking into account the advantages and disadvantages of applying or abolishing the presidential threshold, in order for the purpose of strengthening the presidential system to be achieved. The existence of simultaneous general elections has substantially eliminated the provisions of the presidential threshold, so the threshold requirement to nominate the President and Vice President becomes irrelevant. However, if the legislators demand presidential threshold, the middle path that can be selected is to apply the presidential threshold by using the legislative election 2014 with a record of institutionalizing the coalition.